Efektivitas Komunikasi Pemuka Pendapat Kelompok Tani dalam Menggunakan Teknologi Usahatani Padi (Kasus di Kecamatan Kupang Tengah Kabupaten Kupang NTT) - I. R. Rohi; A. Saleh; R.W.E. Lumintang (Institut Pertanian Bogor, 2009)
Communication effectiveness opinion leader of farmer groups in uses rice farming technology: case at KupangTengah district Kupang regency Nusa Tenggara Timur province. The Research objectives are: (1) to expose opinionleader characteristics, as well as using information source, (2) to detect communication effectiveness among opinionleader, (3) to evaluate applying rice farming technology, (4) to analize to relationship among characteristics,information source, and frequency leader to leader employing, communication effectiveness practicing ricetechnology to farmer at Kupang Tengah district Kupang regency Nusa Tenggara Timur province. Research wasdesigned in descriptive correlation survey method. The data was collecting during March to May 2008.Thepopulation was the entire opinion leader from five rice farmer groups. Total respondents were 99 persons. Data wasanalyzed by rank Spearman statistical test. Result indicated: (1) leader characteristics was potentially enough toapply rice technology, (2) mass media utilization as source of information waslimited, (3) introduce rice technologyby leader, indicating more effective, (4) several characteristics factors which are significantly correlated positivelyas well as negatively to communication effectiveness: social participation, formal education, family size, attitude,social status, farm size, mass media utilization and contact to extension agent.